IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MENINGKATKAN KEDISIPLINAN PESERTA DIDIK MADRASAH IBTIDAIYAH - Abd Rahman (AL-ILMU, 2023)
Students are one of the parents of educational institutions, without students educational institutions cannot be said to be educational institutions, the existence of students in educational institutions is the sole purpose of education being created. The existence of educational institutions for students can actually become an institution of change and the formation of the character of students in accordance with the demands of national education and Islamic education, namely to become students who have akhlakul qarimah through guidance, training and lessons. This research uses descriptive qualitative research where the purpose of this research is to describe research results related to the implementation of character education in improving student discipline at Mis Ar-Rahman Paya Tumpi, the formulation of the problem in this study is, 1. How is the implementation of character education management in increasing the discipline of students at MIS Ar-Rahman, 2. What are the efforts in overcoming the inhibiting factors of the implementation of character education management in increasing the discipline of participants students at MIS Ar Rahman, as for research instruments using interviews, observation and documentation with data analysis using data reduction, data presentation and drawing conclusions from the results of the entire study. The results of the research above can be explained that students need guidance on principles that are in accordance with national education, which have a democratic attitude, so that disciplinary regulations need to be applied to students, as long as the rules that will be carried out do not deviate from religious and state law, as well as madrasah ibtidaiyah Ar-Rahman private sector, in order to implement character education in improving discipline requires efforts and the formation of programs that are more flexible and can be run by MIS Ar-Rahman, both in terms of planning, implementation and evaluation mapping, these three elements become a benchmark for the running of the disciplinary program at Mis Ar-Rahman. Keywords: Character Education, discipline, Basic education